2023
DOI: 10.2478/adms-2023-0023
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of ArC Voltage and Shielding Gas Type on the Microstructure of Wire ArC Additively Manufactured 2209 Duplex Stainless Steel

Dávid Miklós Kemény,
Bence Sándor,
Balázs Varbai
et al.

Abstract: Duplex stainless steels (DSSs) are widely used due to their corrosion resistance. Austenite and ferrite determine the excellent properties. Ferrite provides strength and good corrosion resistance, while austenite provides toughness and weldability. During our research, samples were produced with ER 2209 duplex steel wire using wire arc additive manufacturing (WAAM). Two different 17 V and 19 V arc voltages were used during the production. Two shielding gases were used for each voltage: M12-ArC-2.5 and M12-ArHe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The presence of oxygen enhances the fluidity of the liquid metal and restricts alterations in wall flatness. The effect of the arc voltage and the shielding gas (Ar+2.5CO 2 , Ar+20He+2CO 2 ) on the structure of the 2209 duplex steel during WAAM processing was investigated in a study [22]. It was found that when changing the parameters, it's important to note that an increase in the voltage leads to a higher specific heat input, which results in a longer cooling time (Δt12/8) and a higher austenite content.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of oxygen enhances the fluidity of the liquid metal and restricts alterations in wall flatness. The effect of the arc voltage and the shielding gas (Ar+2.5CO 2 , Ar+20He+2CO 2 ) on the structure of the 2209 duplex steel during WAAM processing was investigated in a study [22]. It was found that when changing the parameters, it's important to note that an increase in the voltage leads to a higher specific heat input, which results in a longer cooling time (Δt12/8) and a higher austenite content.…”
Section: Introductionmentioning
confidence: 99%